Edukacja akademicka przyszłych pracowników socjalnych w zakresie zagadnień prawnych i jej znaczenie dla projektowania efektywnego wsparcia beneficjentów pomocy społecznej - Rajewska de Mezer, Joanna (Studia Edukacyjne, 2019)
This article deals with the problem of academic education of students of Social Work, future social workers, in the field of legal issues. The profession of a social worker requires a broad interdisciplinary knowledge. It consists in providing help to a client in need of support in overcoming life’s hardships, which he cannot overcome alone using his own capabilities, competences and resources.Amon at empowering the client. Problems faced by a social worker when applying the law are connected with a large volume of legal acts, their interpretive unanimity and constant variability (disrupting the sense of stability). The correct application of the law by social workers in the assistance and activation process, requires the appropriate methodical influence in the process of their education, the appropriate selection of issues to be addressed, including problems with which a social worker will have contact in their work. Equally noteworthy is the method of transferring knowledge in the field of legal issues and taking into account the practical aspect of the presented issues. The study analyzed the curricula of selected universities in Poland, in the field of social work, in terms of students’ legal education.